Semiotics of Symbolic Wordplay in the Selected Yorùbá Sports News on Radio Stations in Ìbàdàn, Ọ̀yọ́ State, Nigeria. - Kiaribee , Luqman; ALABI, Monsurat Oritoke (ASEAN Journal of Research, 2025)
Language use in news broadcasting is mainly determined by the themes of discussion. The general belief is that the language of broadcasting is primarily simple, noncritical and self-explanatory. Language use in Yorùbá sports news in recent times has deviated from this norm, making the language of broadcasting more critical. This makes the literary use of language in Yorùbá sports broadcasting apparent. Among the literary expressions employed in making the language of sports news aesthetic is symbolic wordplay. Since the use of this Yorùbá traditional literary device is evident in Yorùbá sports broadcasting, there is a need to study and explain the motive of its use, the forms and the meaning it generates. Three Yorùbá sports news broadcasters were purposively selected from two radio stations across Ìbàdàn metropolis. Two sports news reports were collected from each of the selected broadcasters. These served as the study’s primary data. The study’s secondary data included Yorùbá oral materials used in the analysis. Structuralist semiotics was employed for data analysis. This study revealed that the use of symbolic wordplay is common among the Yorùbá sports news broadcasters. This is employed to signify different things that are central to the news reports. The device constitutes one of the major literary devices employed in Yorùbá sports news broadcasting. The study also affirmed that symbolic wordplay is more used in reporting the Barclays Premier League than other football competition, and it is a means of creating humour in sports news broadcasting.